Observation of electron–phonon coupling and linear dichroism in PL spectra of ultra-small CsPbBr3 nanoparticle solution - Chengqiang Wang; Tao Song; Pingyuan Yan; Shu Hu; Chenhong Xiang; Zihan Wu; Heng Li; Haibin Zhao; Lili Han; Chuanxiang Sheng (eScience, 2023)
Blue-emission (∼480 ​nm) CsPbBr3 nanoparticles with ultra-small size (∼2.1 ​nm) are synthesized using the liquid nitrogen freezing with the ligand of dodecylbenzene sulfonic acid (DBSA). Asymmetric narrow emissions at the low energy side, with the full width at half-maximum of ∼20 ​nm, are observed in solution and film at room temperature. The spectral asymmetry is mainly ascribed to phonon vibronic replica with averaged phonon energy of ∼40 ​meV. Moreover, exciting this CsPbBr3 nanoparticles solution using linearly polarized 6 ns pulsed laser at 355 ​nm, we observe polarized emission with polarization degree (PPL) of ∼7%, and PPL decreases more than 20% in the vibronic progression. However, the PPL goes to zero in frozen solutions as well as in films. Thus we speculate the polarized emission is due to the photoinduced re-alignment of nanoparticles, and the diminished PPL at the phonon side band may be due to the non-adiabatic electronic-to-vibronic transitions. The novel phenomena from the ultra-small CsPbBr3 nanoparticle demonstrated in this work may provide fundamental insights into its photophysics with direct implications for optoelectronics.